We will have the following:
a) f(x) is a linear function:
We find the slope using the two points given:
![m=(70-10)/(2-1)\Rightarrow m=60](https://img.qammunity.org/2023/formulas/mathematics/college/xlyd259et3j1d6b85ixnn2nvrtunjimxyk.png)
Now, we replace in the general formula for a linear function:
![y-y_1=m(x-x_1)\Rightarrow y-10=(60)(x-1)](https://img.qammunity.org/2023/formulas/mathematics/college/b2zh9pdnqd5uo9emq3zuhge2j5en5r7c1y.png)
![\Rightarrow y-10=60x-60\Rightarrow y=60x-50](https://img.qammunity.org/2023/formulas/mathematics/college/og6s6vynwj9l7feijz66rryxwf11zvbmwf.png)
b) f(x) is a power function:
We know taht a power function is given by the general expression:
![f(x)=kx^n](https://img.qammunity.org/2023/formulas/mathematics/college/fit5ozorx205d3eg3wpfgk3o1986b0hhzb.png)
Now, we will have that for each point the following is true:
![\begin{cases}10=k(1)^n \\ \\ 70=k(2)^n\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/1amty9pbyuwrpy573umxkivy32w3dg899o.png)
Now, we solve both for k and equal them:
![\begin{cases}k=(10)/(1^n) \\ \\ k=(70)/(2^n)\end{cases}\Rightarrow(10)/(1^n)=(70)/(2^n)\Rightarrow10\cdot2^n=70\cdot1^n](https://img.qammunity.org/2023/formulas/mathematics/college/qv1vmawrzbsxr3hab6n6ct5enyru3vt3bb.png)
![\Rightarrow\ln (10\cdot2^n)=\ln (70\cdot1^n)\Rightarrow\ln (10)+\ln (2^n)=\ln (70)+\ln (1^n)](https://img.qammunity.org/2023/formulas/mathematics/college/mtmv5xad3gy7lknr968jf2ypuvze3puhde.png)
![\Rightarrow\ln (10)+n\ln (2)=\ln (70)+n\ln (1)\colon\ln (1)=0](https://img.qammunity.org/2023/formulas/mathematics/college/s54ced5d7psv2mw58yaozx4g1l4938b663.png)
So:
![\ln (10)+n\ln (2)=\ln (70)+n\ln (1)\Rightarrow\ln (10)+n\ln (2)=\ln (70)](https://img.qammunity.org/2023/formulas/mathematics/college/k2llp8diht6vuz8wh3m329kq2s3i9trxtx.png)
![\Rightarrow n\ln (2)=\ln (70)-\ln (10)\Rightarrow n\ln (2)=\ln (70/10)](https://img.qammunity.org/2023/formulas/mathematics/college/v5p64xwjw1xtyd8tjdcjptrz5ukaowfw4w.png)
![\Rightarrow n=(\ln (7))/(\ln (2))](https://img.qammunity.org/2023/formulas/mathematics/college/37bx7mgukwcdyl8yvcx05utwds1ddssn2w.png)
Now, we replace this value in one of the expressions and solve for k:
![10=k(1)^(\ln (7)/\ln (2))\Rightarrow k=10](https://img.qammunity.org/2023/formulas/mathematics/college/k1c2ajyr72pxtplga7uuzrbluo2db1tnyb.png)
[1 at any power is also 1], now we write the expression that would be described:
![f(x)=10x^(\ln (7)/\ln (2))](https://img.qammunity.org/2023/formulas/mathematics/college/ba4lu3cjsdcel0b7kzquracc9ftbwgyixa.png)
c) We remember that the general form of a exponential function is givven by:
![f(x)=a\cdot b^x](https://img.qammunity.org/2023/formulas/mathematics/college/53qy1lhggvjad0vnt1ozli3ynbybkwicpn.png)
Now, using this and the two points we calculate:
![\begin{cases}10=a\cdot b^1 \\ \\ 70=a\cdot b^2\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/bv887dvona02tkqsmjs16nvqbys9ohqgns.png)
Now, we solve both for a and equal them:
![\Rightarrow\begin{cases}a=(10)/(b) \\ \\ a=(70)/(b^2)\end{cases}\Rightarrow(10)/(b)=(70)/(b^2)\Rightarrow10b^2=70b](https://img.qammunity.org/2023/formulas/mathematics/college/n74qoxnvt238i4y83cf4hs99a1ws37yy4j.png)
![\Rightarrow10b^2-70b=0\Rightarrow b=\frac{-(-70)\pm\sqrt[]{(-70)^2-4(10)(0)}}{2(10)}](https://img.qammunity.org/2023/formulas/mathematics/college/jsydrxgin0xfhzmr7i5rkqv9v2zk65dutt.png)
![\Rightarrow\begin{cases}b=0 \\ \\ b=7\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/hwvfa2myfvsfn37eq7f2mhvhs2w8hsl4v9.png)
Now, since having a value of "b" equal 0 would make little sense, we work with b = 7. Then we replace in one of the expressions and solve for a, that is:
![\Rightarrow10=a\cdot7^1\Rightarrow7a=10\Rightarrow a=(10)/(7)](https://img.qammunity.org/2023/formulas/mathematics/college/v2xozxqq3be9i01h6f0u3o3dfae4xsgxx3.png)
From this, we will have that the exponential form would be:
![f(x)=(10)/(7)(7)^x](https://img.qammunity.org/2023/formulas/mathematics/college/l5jbqq4m2aqhft4tw5hsopmr5la2ab8myp.png)